Building design can impact every facet of patient safety, sometimes in unexpected way. Are hospital managers and healthcare providers being supported to address this? - Mohd Nawawi, Norwina; Aripin, Srazali (2015)
Buildings are basic shelters. However with time, need and demand buildings had evolved into much sophistication beyond comprehension. Universally, buildings are designed and build physically and environmentally for people to feel safe and secure as end-users or inhabitants. Professionally, professionals are trained with safety in mind in design. Laws and rules in the form of guidelines, acts and best practices speak of safety among other aspects, are mandatory to comply. More so healthcare buildings, strict rules were applied to planning, design and implementation processes until commissioning to ensure functionality that includes safety to end-users especially patients.Good briefing guidelines advise clients to be involved as end-users from the inception of the project to ensure operability and smooth takeover on day one. However, rarely the impact of the building design to patient safety from one design to another design, after it is being used, are imparted officially. The objective of this presentation is to explore what are the unexpected way patient safety may be impacted by building design and how the information may assist hospital managers and healthcare providers to address the issue effectively. Through case studies, experiences and literature review the presentation will inform the tangible and the intangible impact foresee during the different stages of generic hospital design and subsequent post occupancy evaluation of selected healthcare facilities. The presentation will discuss and share the various outcome and recommendations made from selected research and projects. The unexpected impact of the design may be both positive and negative. Expected findings include the need for end-users and design team-active participation from the inception to the completion of the project and the team's ability to communicate effectively as a team. The sustainability of briefing and commissioning to next in line; the need to conduct the post-occupancy evaluation as evidence-based in the patient areas as an official pursuit has been lamented many times. Unexpected finding goes beyond physical building to reviewing the operational policies that may have had impacted the building design in the first place and the composition of the design team. Building once designed stays. People’s behaviour and culture are adaptable for better or worse. Let us ponder Sir Winston Churchill’s statement “ We shaped our building. Thereafter they shape us”.